(untitled) (Ustozlar uchun, 2025)
Abstract. This article analyzes the role of genetic engineering in agriculture, its ecological and social impacts, as well as international perspectives on the issue. The goal is to increase productivity through genetically modified organisms (GMOs) and create plants resistant to pests and herbicides. However, the long-term consequences of this technology have not yet been fully studied. The article also highlights the position of the WWF regarding genetic engineering, as well as the level of GMO cultivation in various countries.